Vibrio cholerae non-O1/non-O139 infection in fish in the Czech Republic - J. Rehulka; P. Petras; M. Marejkova; E. Aldova (Veterinární Medicína, 2015)
Pathogenic Vibrio cholerae non-O1/non-O139 was isolated from the fry of the Cardinal tetra, Paracheirodon axelrodi and in adult Raphael catfish, Platydoras costatus kept in aquarium conditions. Further, an outbreak of vibriosis occurred in the wild populations of common nase, Chondrostoma nasus; chub, Squalius cephalus; gudgeon, Gobio gobio; stone loach, Barbatula barbatula; barbel, Barbus barbus; European grayling, Thymallus thymallus; schneider, Alburnoides bipunctatus; and brown trout, Salmo trutta morpha trutta. Mortality was not observed in the Eurasian minnow, Phoxinus phoxinus. During 14 days the acute rather than the sub-acute-to-chronic process of the disease prevailed with severe gross lesions in common nase and chub (diffused and focal haemorrhages, erythema and hyperaemia located especially in the abdominal region, within the mouth and at the base of fins). Only in the infection of the common nase was the whole eye affected, causing rupture of the globe and destruction of ocular structures. Gross pathological lesions in experimentally infected fish manifested themselves as gasping, erratic swimming, congested capillaries on the wall of the air bladder and fluid and blood accumulation in the abdominal cavity. Injection of 2 × 104 bacteria (common carp, rainbow trout) and injection of 2 × 108 bacteria (common nase) via i.p. route resulted in mortalities within 120 hrs and 16 h, respectively. Factors underlying the rise of infection are discussed, including an extraordinary increase in water temperature (20 °C to 23 °C), fluctuating oxygen content and low water level which contributed to increasing the concentration of the faecal contamination of water: these factors could stimulate the virulence of the vibrios, which survive in aquatic flora and fauna and in the biofilm on the surface of sediments.